Ultrasound diagnosis of hydrops fetalis in a crossbred bitch - Cahua U., Jacqueline (2021)
It is described describe the clinical case of a 1-year-old crossbreed bitch, with a dystocic delivery of 12 hours that presented a fetus in a foot position in the pelvic canal. The ultrasound study revealed two apparently normal live fetuses and two with severe anasarca, pleural effusion and ascites, one of which had caused dystocia. The patient was subjected to a cesarean section. The ultrasound findings were confirmed by necropsy of the fetuses with dropsy. In addition, two of the fetuses presented palatoschisis.